2009
DOI: 10.1098/rspb.2008.1744
|View full text |Cite
|
Sign up to set email alerts
|

Orienting to threat: faster localization of fearful facial expressions and body postures revealed by saccadic eye movements

Abstract: Most studies investigating speeded orientation towards threat have used manual responses. By measuring orienting behaviour using eye movements a more direct and ecologically valid measure of attention can be made. Here, we used a forced-choice saccadic and manual localization task to investigate the speed of discrimination for fearful and neutral body and face images. Fearful/neutral body or face pairs were bilaterally presented for either 20 or 500 ms. Results showed faster saccadic orienting to fearful body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
128
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(143 citation statements)
references
References 54 publications
12
128
1
1
Order By: Relevance
“…Specifically, contrasts revealed that high expressive pain faces were rated significantly higher (M = 7.43; SD = .97) than moderate expressive pain faces (M = 5.55, SD = 1.30; F(1,34) = 631.76, p < .0001). Moderate expressive pain faces, in turn, were rated significantly higher than low expressive pain faces (M = 3.81, SD = 1.22; F(1,34) = 608.96, p < .0001) and low expressive pain faces were also rated significantly higher than neutral faces (M = .89, SD = .95; F (1,34) =426.06, p < .0001). Adding pain catastrophizing and pain intensity as covariates to the repeated measures ANOVA revealed no significant main effects or interactions (all F ≤ |1.52|, ns) indicating that ratings of faces" pain intensity were not affected by observer"s own pain catastrophizing and experienced personal pain intensity.…”
Section: Picture Ratingsmentioning
confidence: 87%
“…Specifically, contrasts revealed that high expressive pain faces were rated significantly higher (M = 7.43; SD = .97) than moderate expressive pain faces (M = 5.55, SD = 1.30; F(1,34) = 631.76, p < .0001). Moderate expressive pain faces, in turn, were rated significantly higher than low expressive pain faces (M = 3.81, SD = 1.22; F(1,34) = 608.96, p < .0001) and low expressive pain faces were also rated significantly higher than neutral faces (M = .89, SD = .95; F (1,34) =426.06, p < .0001). Adding pain catastrophizing and pain intensity as covariates to the repeated measures ANOVA revealed no significant main effects or interactions (all F ≤ |1.52|, ns) indicating that ratings of faces" pain intensity were not affected by observer"s own pain catastrophizing and experienced personal pain intensity.…”
Section: Picture Ratingsmentioning
confidence: 87%
“…A number of previous studies on emotional modulation of eye-movement behavior found evidence for faster detection of emotional stimuli (e.g., Bannerman, Milders, de Gelder, & Sahraie, 2009;Bannerman, Milders, & Sahraiem, 2009;Kissler & Keil, 2008;LoBue, Matthews, Harvey, & Stark, 2014). For example, Bannerman, Milders, de Gelder, & showed a decrease in saccade latency when a saccade is directed to the location of a threatening stimulus relative to a nonthreatening stimulus.…”
mentioning
confidence: 99%
“…For example, Bannerman, Milders, de Gelder, & showed a decrease in saccade latency when a saccade is directed to the location of a threatening stimulus relative to a nonthreatening stimulus. Other studies found evidence for longer fixation durations on emotional relative to neutral stimuli in free-viewing paradigms (e.g., Calvo & Lang, 2004;Humphrey, Underwood, & Lambert, 2012;Lang, Greenwald, Bradley, & Hamm, 1993), suggesting delayed disengagement from an emotional stimulus (Fox, Russo, Bowles, & Dutton, 2001;Fox, Russo, & Dutton, 2002).…”
mentioning
confidence: 99%
See 2 more Smart Citations